Predictive role of modifiable factors in stroke: an umbrella review. Issue 6 (16th June 2022) - Wang, Xiaotong; Liang, Man; Zeng, Fanxin; Wang, Yue; Yang, Yuetian; Nie, Fangfang; Shang, Mengke; Ta, Na; Wen, Lu; Ou, Lanxin; Yang, Zhibin; Liu, Wanyang
Abstract : Background: A growing number of meta-analyses reviewed the existing associations between modifiable factors and stroke. However, the methodological quality of them and quality of evidence remain to be assessed by validated tools. Thus, this umbrella review was conducted to consolidate evidence from systematic reviews and meta-analyses of cohort studies investigating the association between modifiable factors and incidence of stroke. Methods: PubMed, Web of Science, Embase, Wanfang and China National Knowledge Infrastructure databases for systematic reviews and meta-analyses of cohort studies from inception until March 2021. Assess the methodological quality of systematic reviews 2 was used to evaluate the methodological quality of each included published meta-analysis. Excess significance test was used to investigate whether the observed number of studies (O) with nominally significant results ('positive' studies, p<0.05) was larger than the expected number of significant results (E). Statistically significant (p<0.05) associations were rated into five levels (strong, highly suggestive, suggestive, weak and no) using specific criteria. Sensitivity analyses were performed. Results: 2478 records were identified through database searching. At last, 49 meta-analyses including 70 modifiable factors and approximately 856 801 stroke cases were included in the present review. The methodological quality of three meta-analyses was low, while others were critically low. Evidence of walking pace was strong. High suggestive evidence mainly included total meat, processes meat, chocolate, sodium, obesity, pulse pressure, systolic blood pressure, diastolic blood pressure, sleep duration and smoking. Suggestive evidence mainly included dietary approaches to stop hypertension (DASH) diet, vitamin C, magnesium, depression and particulate matter 2.5. After sensitivity analyses, evidence of DASH diet, magnesium and depression turned to weak. No publication bias existed, except only one study which could be explained by reporting bias. Discussion: Diet with rich macronutrients and micronutrients, healthy dietary patterns and favourable physical, emotional health and environmental management should be promoted to decrease the burden of stroke. PROSPERO registration number: CRD42021249921.